Intellectual disabilities: improving access to therapeutic communities. Issue 6 (November 2016) - Shaddel, Farshad; Ghazirad, Marjan; Banerjee, Subimal; Newrith, Christopher
Abstract : Access to specialised therapeutic communities (TCs) for people with intellectual disabilities (IDs) such as 'Camphill communities' and 'TCs plus' is limited and patchy in the UK. Nonetheless, the emphasis for some time now has been to enable people with IDs to access mainstream services, which have a legal duty to make reasonable adjustments to facilitate this. Here, the authors propose a set of recommendations in order to improve the access of people with ID to mainstream therapeutic communities and enhance the services they receive.